The anterior cingulate cortex contributes to the analgesic rather than the anxiolytic effects of duloxetine in chronic pain-induced anxiety - Li, Chenglin; Ni, Kaiji; Qi, Meiru; Li, Jie; Yang, Kexin; Luo, Yanli (Frontiers in Neuroscience, 2022)
Mood disorders are commonly found in people suffering from chronic pain. Serotonin-norepinephrine reuptake inhibitors (SNRIs) has displayed its potential in alleviating chronic pain and is the first-line option for anxiety-disorder. Anterior cingulate cortex (ACC) plays an important role in chronic pain induced anxiety, but its role in the therapeutic effects of SNRIs remains largely unclear. In this current study, anxiety-like behaviors were successfully induced in inflammatory pain modeled mice and such behaviors were reversed by intraperitoneal injection of duloxetine while the mechanical hyperalgesia was also improved. Then we locally infused duloxetine in ACC only to find out its analgesic effect. Furthermore, we used fiber photometry to find decreased glutamatergic excitability and enhanced serotonin concentration in ACC after intraperitoneal injection of duloxetine. Taken together, this study proposed a potential mechanism on the analgesic effect of duloxetine and shed light on further studies on the mechanism of its anxiolytic effect.